Teksti lasīšanai klasiskajā sīriešu valodā - Zeps, Dainis (My University, 2017)
Parallel texts from New Testatment in Syriac and Greek for home reading or in class in Classical Syriac, composed by Dainis Zeps.
Texts for Readinga in Classical Syriac
Keywords: classical syriac